2023
DOI: 10.1002/ccd.30745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of interventions for intermediate to high‐risk pulmonary embolism: A network meta‐analysis

Abstract: Background Multiple interventions, including catheter‐directed therapy (CDT), systemic thrombolysis (ST), surgical embolectomy (SE), and therapeutic anticoagulation (AC) have been used to treat intermediate to high‐risk pulmonary embolism (PE), but the most effective and safest treatment remains unclear. Our study aimed to investigate the efficacy and safety outcomes of each intervention. Methods We queried PubMed and EMBASE in January 2023 and performed a network meta‐analysis of observational studies and ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…4 A recent network meta-analysis of observational studies and RCTs involving patients with intermediate-to high-risk PE showed a reduced mortality rate when utilising CDT compared with other therapeutic procedures without significant additional bleeding risk. 35 The indication for catheter-based treatment of acute PE requires-like IV thrombolysis-a manifest or impending circulatory instability. It is therefore an acute situation, so that reperfusion treatment (in analogy to acute ST elevation myocardial infarction) should begin as soon as possible after indication.…”
Section: Absolute Contraindicationmentioning
confidence: 99%
“…4 A recent network meta-analysis of observational studies and RCTs involving patients with intermediate-to high-risk PE showed a reduced mortality rate when utilising CDT compared with other therapeutic procedures without significant additional bleeding risk. 35 The indication for catheter-based treatment of acute PE requires-like IV thrombolysis-a manifest or impending circulatory instability. It is therefore an acute situation, so that reperfusion treatment (in analogy to acute ST elevation myocardial infarction) should begin as soon as possible after indication.…”
Section: Absolute Contraindicationmentioning
confidence: 99%
“…In a network meta-analysis comparing the CDT, systemic TT, surgical embolectomy, and anticoagulant therapies in patients at IR to HR groups, CDT was found to be associated with significant reductions in in-hospital mortality, PE recurrence, and major bleeding rates as compared to the other 3 treatment modalities and reductions in long-term mortality equivalent to surgical embolectomy. 47 …”
Section: Mechanical Thrombectomymentioning
confidence: 99%
“…3 While ST is recommended as first-line treatment for hemodynamically unstable PE, it has been estimated that more than half of high-risk PE patients do not received ST due to absolute or relative contraindications. 4 Though the use catheter-directed thrombolysis (CDT) allows for a reduced dose of thrombolytic therapy and has been associated with improved outcomes compared to ST, [5][6][7] it is still associated with major bleeding rates of up to 10%, including a risk of intracerebral hemorrhage (ICH) of up to 2%. 2,7 These concerns have led to growing interest in percutaneous mechanical thrombectomy (MT) as an alternative therapy for this population.…”
Section: Introductionmentioning
confidence: 99%